Built for speed: musculoskeletal structure and sprinting ability - Lee, S. S. M.; Piazza, S. J. (The Journal of Experimental Biology, 2009)
The musculoskeletal structure of the foot and ankle has the potential to influence human sprinting performance in complex ways. A large Achilles' tendon moment arm improves the mechanical advantage of the triceps surae but also produces larger shortening velocity during rapid plantarflexion, which detracts from the force-generating capacity of the plantarflexors. The lever arm of the ground reaction force that resists the muscular plantarflexor moment during propulsive push-off is constrained in part by the skeletal structure of the foot. In this study, we measured the plantarflexion moment arms of the Achilles' tendon, lateral gastrocnemius fascicle lengths and pennation angles, and anthropometric characteristics of the foot and lower leg in collegiate sprinters and height-matched non-sprinters. The Achilles' tendon moment arms of the sprinters were 25% smaller on average in sprinters than in non-sprinters (P<0.001) whereas the sprinters' fascicles were 11% longer on average (P=0.024). The ratio of fascicle length to moment arm was 50% larger in sprinters (P<0.001). Sprinters were found to have longer toes (P=0.032) and shorter lower legs (P=0.026) than non sprinters. A simple computer simulation of the sprint push-off demonstrated that shorter plantarflexor moment arms and longer toes, like those measured in sprinters, permit greater generation of forward impulse. Simulated propulsion was enhanced in both cases by increasing the `gear ratio' of the foot, thus maintaining plantarflexor fibre length and reducing peak fibre shortening velocity. Longer toes especially prolonged the time of contact, giving greater time for forward acceleration by propulsive ground reaction force.